An evaluation of the village regroupment concept: Mukim Binjal, Kedah / Abdul Halim Abu - Abu, Abdul Halim (1985)
Development of human settlements including housing, community facilities, transportation, industrial and commercial facilities, poses some of the most basic questions of national development. What is needed is that in setting overall objectives, and in developing targets and strategies for economic and social development, the role of human settlements in development be better understood so as to explicit/ derive the corresponding subsidiary goals, targets and strategies for the development of human settlements. The new directions in rural settlement development of the village regroupment concept in introduced under the Fouth Malaysian Plan-Mid Term Review (1980 - 1985), Under this new strategy, large number of email scattered rural settlements will be grouped into rural centres which act as a Rural Growth Centre (ROC) where infrastructural facilities can be more efficiently and economically provided. Thus, directly the concept will create the urbanization of the traditional village or kampung, in other words, creation of rural urbanization. Again, the efforts towards regeneration and development are generally carried out actively by the goverments…